Optimization of Air Ventilation in a Commercial Futsal Building in Makassar - Ismajaya, Muh. Aryanugraha; Tenriola, Raeny; Asnur, Moeh. Kay Muddin; Helmy, Ahnaf Riyandirga Ariyansyah Putra (Nature: National Academic Journal of Architecture, 2025)
Indoor air quality plays a vital role in ensuring comfort and maintaining the health of users in enclosed sports facilities, such as indoor futsal courts. Proper air circulation significantly contributes to thermal comfort and reduces health risks associated with inadequate ventilation. However, this aspect is often neglected in the design of such buildings. This study aims to: (1) analyze the performance of air circulation in indoor futsal buildings, (2) assess indoor air quality, and (3) develop a design model that optimizes airflow using computational simulation. The research methodology included field surveys and direct measurements of building and ventilation opening dimensions, air velocity, temperature, and concentrations of CO and CO₂. Simulations were performed by adding new inlets and outlets equal in area to the existing ones but repositioned strategically—additional inlets were placed at 6.70 meters above the floor, and outlets were located 1 meter above the floor. The third simulation scenario showed a significant improvement in airflow speed at the central part of the building, ranging between 0.7 m/s and 1.5 m/s. By increasing the total inlet area to 271.32 m² and the total outlet area to 171.6 m², with incoming airflow speeds of 2.7 m/s, a more effective and evenly distributed indoor air circulation was achieved. These findings confirm that modifying the placement and sizing of natural ventilation elements can substantially enhance airflow performance in indoor futsal facilities. The proposed design model contributes meaningfully to architectural practices aimed at creating healthier sports facilities that effectively respond to passive ventilation requirements and may serve as a reference for the design of similar buildings in tropical climate regions.